Reproductive Health Literacy of Adolescents at Public Islamic School: A Cross-Sectional Study in Indonesia - Wardiati Wardiati; Riza Septiani; Agustina Agustina; Putri Ariscasari; Nopa Arlianti; Tiara Mairani (Program Studi Kesehatan Masyarakat UIN Alauddin Makassar, 2023)
Inadequate adolescents’ reproductive health literacy is a serious problem that requires urgent attention from all stakeholders. Adolescents with limited knowledge of reproductive health are more prone to facing various health problems. Therefore, this study aims to determine the level of adolescents reproductive health literacy and its associated factors. An analytical approach was adopted with a cross-sectional design. The target population consisted of female students in classes XI and XII, at Public Islamic Senior High School 2 Banda Aceh, totaling 242 students. An accidental sampling method was utilized to select the sample, and the number of respondents was 150 students. The data obtained were analyzed using simple linear and multiple linear regression tests. The results showed that the level of reproductive health literacy was moderate (M=3.20; SD: 0.70 on a scale of 5), while the associated factors included family role (β=0.397; p-value:0.001), age (β=0.263; p-value:0.001), and peer support (β=0.259; p-value:0.001). These variables accounted for 43.4% of the variance in adolescents reproductive health literacy (R2:0.434). Based on the results, it was concluded that the level of adolescents reproductive health literacy was insufficient, and factors correlated to this problem included family role, age, and peer support.